Fabrication of rutile TiO2 nanorod arrays on a copper substrate for high-performance lithium-ion batteries. Issue 60 (9th June 2016) - Liu, Guanrao; Zhang, Shichao; Wu, Xiaomeng; Lin, Ruoxu
Abstract : TiO2 nanorods array has been prepared directly on flexible copper substrate via in situ synthesis, presenting enormous potentials in LIBs. Abstract : A rutile TiO2 nanorod array has been successfully prepared on a flexible copper substrate and demonstrated as a high-performance anode material for lithium-ion batteries. The prepared materials exhibit excellent electrochemical performance, which depends crucially on the structural parameters and the large specific surface area of the array.